The acute effect of exercise intensity on peripheral and cerebral vascular function in healthy adults - Weston, Max E.; Koep, Jodie L.; Lester, Alice B.; Barker, Alan R.; Bond, Bert (Journal of applied physiology (1985), 2022)
This is the first study to identify that acute improvements in peripheral vascular function following high-intensity interval exercise are not mirrored by improvements in cerebrovascular reactivity in healthy young adults. High-intensity interval exercise completed at both 75% and 90% V̇o 2max increased brachial artery flow-mediated dilation 1 and 3 h following exercise, compared with continuous moderate-intensity exercise and a sedentary control condition. By contrast, cerebrovascular reactivity was unchanged following all four conditions. The acute effect of exercise intensity on cerebrovascular reactivity and whether this mirrors changes in peripheral vascular function have not been investigated. The aim of this study was to explore the acute effect of exercise intensity on cerebrovascular reactivity (CVR) and peripheral vascular function in healthy young adults ( n = 10, 6 females, 22.7 ± 3.5 yr). Participants completed four experimental conditions on separate days: high-intensity interval exercise (HIIE) with intervals performed at 75% maximal oxygen uptake (V̇o 2max ; HIIE1), HIIE with intervals performed at 90% V̇o 2max (HIIE2), continuous moderate-intensity exercise (MIE) at 60% V̇o 2max and a sedentary control condition (CON). All exercise conditions were completed on a cycle ergometer and matched for time (30 min) and average intensity (60% V̇o 2max ). Brachial artery flow-mediated dilation (FMD) and CVR of the middle cerebral artery were measured before exercise, and 1- and 3-h after exercise. CVR was assessed using transcranial Doppler ultrasonography to both hypercapnia (6% carbon dioxide breathing) and hypocapnia (hyperventilation). FMD was significantly elevated above baseline 1 and 3 h following both HIIE conditions ( P < 0.05), but FMD was unchanged following the MIE and CON trials ( P > 0.33). CVR to both hypercapnia and hypocapnia, and when expressed across the end-tidal CO 2 range, was unchanged in all conditions, at all time points (all P > 0.14). In conclusion, these novel findings show that the acute increases in peripheral vascular function following HIIE, compared with MIE, were not mirrored by changes in cerebrovascular reactivity, which was unaltered following all exercise conditions in healthy young adults. NEW & NOTEWORTHY This is the first study to identify that acute improvements in peripheral vascular function following high-intensity interval exercise are not mirrored by improvements in cerebrovascular reactivity in healthy young adults. High-intensity interval exercise completed at both 75% and 90% V̇o 2max increased brachial artery flow-mediated dilation 1 and 3 h following exercise, compared with continuous moderate-intensity exercise and a sedentary control condition. By contrast, cerebrovascular reactivity was unchanged following all four conditions.